ON THE CONCEPT OF CONTEMPORARY STATE POLICY IN THE SPHERE OF IT - Elena S. Ustinovich (Сравнительная политика, 2015)
Article retractedUsing a comparative perspective the author reviews conceptual approaches of Russian and foreign researchers to the definition of state information policy. Author also formulates her own definition of state policy in the sphere of information technologies (IT).